2006
DOI: 10.1002/pi.1999
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antimicrobial activity of transition metal chelated thiourea‐formaldehyde resin

Abstract: A polymeric ligand (thiourea‐formaldehyde resin ‐ TUFR) bearing nitrogen and sulfur donor groups was synthesized by the polycondensation of thiourea and formaldehyde in acidic medium and its polychelates were prepared in alcoholic solution of metal ions such as Mn(II), Co(II), Ni(II), Cu(II) and Zn(II). The TUFR polymeric ligand and its TUFR‐M(II) polychelates were characterized with micro‐analytical analysis and spectral studies. The FTIR spectra of polychelates indicated that the metal ions were coordinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…This result revealed that PETUNi shows better heat resistant characteristics than PETU due to the coordination of metal ions [49].…”
Section: Synthesismentioning
confidence: 62%
“…This result revealed that PETUNi shows better heat resistant characteristics than PETU due to the coordination of metal ions [49].…”
Section: Synthesismentioning
confidence: 62%
“…In all the polymer-metal complexes, coordination of metal ion to the polymeric ligand was further supported by the appearance of ν M-S and ν M-N stretching vibrations in 630-620 and 510-490 cm −1 regions, respectively. [31] The synthesized polymers were followed by 13 C NMR and 1 H NMR. Figure 1 The electronic spectra of all the synthesized polymers were recorded in DMSO solution.…”
Section: Characterization Of the Polymer And Its Polymer Metal Complexmentioning
confidence: 99%
“…Schiff-base polyurethanes have also been established [6,7] and thiosemicarbazide and thiosemicarbazone Schiff bases have gained special attention due to their activity against protozoa, influenza, small pox, malaria, cancer, and tuberculosis [8]. Recently, we synthesized a series of antimicrobial coordination polymers which possess promising antimicrobial properties [9][10][11][12]. Owing to the wide range of microbial properties of thiosemicarbazides and their ability to form chelates with metal ions, in this study we report the syntheses and characterizations of metal-containing polyurethanes.…”
Section: Introductionmentioning
confidence: 99%